Design and Implementation of E-Campus Ontology with a Hybrid Software Engineering Methodology - Jacksi, karwan (Science Journal of University of Zakho, 2019)
Semantic Web according to the vision of the W3C is the future of WWW (or Web). It is an extension of the current Web through standards by the W3C. Data of the Semantic Web has well-defined meanings, can be understood by devices and allows machines and people to work in collaboration. Ontologies are vital components of the Semantic Web infrastructure and are more often recognized as the backbone of the Semantic Web. Although numerous developments occur in the field of developing ontologies along the lines with the Semantic Web implementation, but standardizing the process models, tools and methodologies need to be improved in the future. In literature, experts in ontology engineering have stated that setting a methodology for developing ontology applications with support of integrated tools is an essential task for ontology engineering to be succeeded. In this paper, an e-campus ontology for educational purposes is designed and implemented, and mainly focused on the learning hierarchy of C-sharp programming language. A hybrid methodology based on software engineering approaches for developing ontologies is presented. Finally, the developed methodology is applied on the implemented ontology.